2012
DOI: 10.1017/thg.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Strabismus: Genetic Influence Is Specific to Eso-Deviation and Independent of Refractive Error

Abstract: Strabismus represents a complex oculomotor disorder characterized by the deviation of one or both eyes and poor vision. A more sophisticated understanding of the genetic liability of strabismus is required to guide searches for associated molecular variants. In this classical twin study of 1,462 twin pairs, we examined the relative influence of genes and environment in comitant strabismus, and the degree to which these influences can be explained by factors in common with refractive error. Participants were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…Recently, researchers have examined heritability of visual processing using modern behavioural-genetic methods (Wilmer, 2008). Examples of this work include studies reporting strong and significant heritability for strabismus, human face recognition, and refractive error, but weak heritability for phoria or aesthetic preferences for faces (Germine et al, 2015; Sanfilippo et al, 2012; Wilmer & Backus, 2009; Wilmer, Germine, Chabris, et al, 2010; Wilmer, Germine, Loken, et al, 2010; Yovel, Wilmer, & Duchaine, 2014). …”
Section: The Value Of Research On Individual Differencesmentioning
confidence: 99%
“…Recently, researchers have examined heritability of visual processing using modern behavioural-genetic methods (Wilmer, 2008). Examples of this work include studies reporting strong and significant heritability for strabismus, human face recognition, and refractive error, but weak heritability for phoria or aesthetic preferences for faces (Germine et al, 2015; Sanfilippo et al, 2012; Wilmer & Backus, 2009; Wilmer, Germine, Chabris, et al, 2010; Wilmer, Germine, Loken, et al, 2010; Yovel, Wilmer, & Duchaine, 2014). …”
Section: The Value Of Research On Individual Differencesmentioning
confidence: 99%
“…In accommodative esotropia, the risk decreases to 7.5% for second degree relatives and to 4.8% for third degree relatives. In twin studies, it has been shown that there is a specific genetic influence for eso-deviation which is independent of the refractive error (Sanfilippo et al, 2012). The heritability of eso-deviation is estimated as 64% in a cohort of 1462 twin pairs with a prevalence of 8.6% of eso-deviation, the correlation being significantly greater in monozygotic twins ( r = 0.65) than in dizygotic twins ( r = 0.33).…”
Section: Peripheral and Genetic Origins Of Strabismusmentioning
confidence: 99%
“…1 Both genetic and environmental factors contribute to strabismus, 24 but in contrast to the rare forms of congenital strabismus, 5 the genetics and molecular mechanisms of common strabismus are not well understood. 6 The etiology of strabismus involves multiple components of the oculomotor system, from the extraocular muscles (EOMs) to visual cortex.…”
mentioning
confidence: 99%